Ultrasonographic Imaging of Normal and Impacted Omasum in Indian Crossbred Cows - Sheikh Imran; S. P. Tyagi; Amit Kumar; Shivali Sharma (Veterinary Medicine International)
Omasal impaction is a serious disease problem in cattle in India, but it is difficult to diagnose clinically. Ultrasonography has been proposed for the noninvasive evaluation of omasal disease. The objectives of this study were to compare the in vitro and in vivo ultrasonographic appearance of the omasum and to compare omasal appearance, limits, and size in clinically healthy cows with those in cows having confirmed omasal impaction. A 3.5 MHz curvilinear transducer was used to image and record the appearance of the omasum in vitro in a water bath, and its appearance, dorsal and ventral limits, and size in 10 healthy Indian Jersey/Red Sindhi crossbred cows. The results were compared with the ultrasonographic data collected from 5 cows with omasal impaction, as confirmed at necropsy. On moving the transducer dorsoventrally in each intercostal space and below the costal arch, the wall of omasum could be seen as an echogenic arc-like structure. The difference between mean dorsoventral extents of the normal and impacted omasums was statistically insignificant. These results suggest that ultrasonographic imaging may not be useful in the diagnosis of omasal impaction in Indian crossbred cows, however, additional studies may be warranted.